Freshwater Reservoir Effect on Redating of Eurasian Steppe Cultures: First Results for Eneolithic and Early Bronze Age Northeast Kazakhstan. Issue 4 (2015) - Svyatko, Svetlana V; Mertz, Ilya V; Reimer, Paula J
Abstract : Freshwater reservoir effects (FRE) can cause problems when radiocarbon dating human skeletal material from the Eurasian steppe. This article presents the first results of research into the extent of the FRE in the sites of Borly 4 (Eneolithic) and Shauke 1 and 8b (Early Bronze Age), northeastern Kazakhstan. Accelerator mass spectrometry (AMS) 14 C dating and stable isotope (δ 13 C, δ 15 N) analysis of associated groups of samples (32 samples, 11 groups in total) demonstrate the following: (a) the diet of the humans and fauna analyzed was based on the C3 foodchain with no evidence of a C4 plant (such as millet) contribution; aquatic resources apparently were a continuous dietary feature for the humans; (b) the first 14 C dates obtained for the Upper and Middle Irtysh River region attribute the Eneolithic period of the area to the 34th to 30th centuries BC, and the Early Bronze Age to the 25th to 20th centuries BC, with a 450-yr hiatus between the two periods; (c) the maximum fish-herbivore freshwater reservoir offset observed equals 301 ± 47 14 C yr. As such, 14 C dates from aquatic and human samples from the area need to be interpreted with caution as they are likely to be affected by the offset (i.e. appear older). The article also discusses the effect of a sodium hydroxide (NaOH) wash on δ 13 C, δ 15 N, C:Natomic levels and collagen yields of the bone samples. Our results indicate a minor but significant effect of NaOH treatment only on C:Natomic ratios of the samples.